2007
DOI: 10.1007/s11064-007-9293-1
|View full text |Cite
|
Sign up to set email alerts
|

ADAM23 Plays Multiple Roles in Neuronal Differentiation of P19 Embryonal Carcinoma cells

Abstract: ADAM23, belonging to ADAM (A Disintegrin And Metalloprotease) protein family, is mainly expressed in brain. P19 cells could differentiate into neuroectodermal cell lineage after cell aggregates have been induced by retinoic acid (RA). In this report, we show that the post-transcriptional and post-translational processes of ADAM23 are regulated during the differentiation of P19 cells. In P19-derived neurons, ADAM23 is polarized distributed in the proximal part. To explore the possible roles of ADAM23 during P19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…ADAM23-deficient mice show tremor and strict ataxia and die within two weeks after birth [14]. Like the previous studies [62,63], we found that ADAM23 is expressed in two forms and its expression is regulated at different developmental stages (Fig. 8).…”
Section: Adam23supporting
confidence: 85%
See 1 more Smart Citation
“…ADAM23-deficient mice show tremor and strict ataxia and die within two weeks after birth [14]. Like the previous studies [62,63], we found that ADAM23 is expressed in two forms and its expression is regulated at different developmental stages (Fig. 8).…”
Section: Adam23supporting
confidence: 85%
“…ADAM23 appears during the differentiation of P19 cells and is involved in the formation of neurites, where ADAM23 is asymmetrically distributed [62]. ADAM23-deficient mice show tremor and strict ataxia and die within two weeks after birth [14].…”
Section: Adam23mentioning
confidence: 99%
“…ADAM23 is expressed predominately as a membrane-bound receptor that localizes to sites of intercellular contact [6]. Studies have further reported that ADAM23 plays an important role in CNS processes [6,8], with loss in function leading to tremors and epileptic episodes [9]. Studies have further reported that ADAM23 plays an important role in CNS processes [6,8], with loss in function leading to tremors and epileptic episodes [9].…”
Section: Introductionmentioning
confidence: 99%
“…ADAM10 sheds ephrinA 2 inducing ephrinA2-mediated axon repulsion (Hattori, 2000) and ADAM10 is required for the formation of the optic projection to the tectum (Chen at al., 2007). Finally, ADAM23 is involved in neuronal differentiation of P19 cells (Sun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%